A Comprehensive Review on Extraction, Structure, Detection, Bioactivity, and Metabolism of Flavonoids from Sea Buckthorn (Hippophae rhamnoides L.). (14th March 2023) - He, Nengxin; Wang, Qinyuan; Huang, Huilian; Chen, Jie; Wu, Guang; Zhu, Meining; Shao, Feng; Yan, Zhihong; Sang, Zhipei; Cao, Lan; Wei, Rongrui; Ma, Qinge
Abstract : Sea buckthorn ( Hippophae rhamnoides L.) is an important plant with homology of medicine and food. It has rich nutritional and medicinal properties. It is used as a traditional Chinese medicine with therapeutic functions of invigorating spleen, relieving cough, eliminating food, eliminating phlegm, dispersing blood stasis, and promoting blood circulation. This review comprehensively summarized flavonoids from sea buckthorn ( Hippophae rhamnoides L.), including extraction methods (solvent extraction, ultrasound-assisted extraction, microwave-assisted extraction, enzyme-assisted extraction, and collaborative extraction), two structure types (18 flavone aglycones and 81 flavone glycosides), detection methods (UV, HPLC, and NMR), bioactivities (antiviral, anti-inflammatory, hepatoprotective, weight-reducing, and hypoglycemic activities), and physiological metabolisms (most of flavonoids are converted into small molecule monophenolic acids through intestinal microbial catabolism). It will supply an important theoretical basis and valuable reference for researching and exploiting sea buckthorn ( Hippophae rhamnoides L.) in the future. Practical Applications . Sea buckthorn ( Hippophae rhamnoides L.) is an edible and medical plant with many functional properties. A comprehensive review on extraction, structure, detection, bioactivity, and metabolism of flavonoids from sea buckthorn ( Hippophae rhamnoides L.) was made in this paper. This review will provide an important foundation for further studies of sea buckthorn ( Hippophae rhamnoides L.) focusing on its development and utilization.